Miejsce słuszności i innych ocen podstawowych w wykładni operatywnej prawa podatkowego - Wirski, Jakub (Kwartalnik Prawa Podatkowego, 2016)
The aim of this article is to determine bases of the application and functions of equity in the operative interpretation of the tax law. The Author is of the opinion that equity should be taken into account in the process of the interpretation of the tax law. Even though a general equity clause does not exist in this area, there are theoretical bases, which allow to apply rules of equity in the process of the operative interpretation of the tax law. This conclusion comes from non-linguistic directives of interpretation as well as from the character of the tax law (especially from its interference). The article describes also constraints in the application of rules of equity in this respect.